Clinical and mycological analysis on the occurrence of superficial mycosis with special emphasis on dermatophytes - Manjula Vagarali; Sharada C Metgud; Soumya S (Al Ameen Medical College, 2020)
Background: Superficial mycosis is prevalent in tropical and subtropical countries including India where heat and humidity play an important role in promoting growth of these fungi. Objectives: To identify superficial mycotic infections and correlate clinical types with dermatophytes. Material and methods: A total of 112 samples were collected from patients clinically diagnosed to have superficial mycotic infections of hair, nail and skin, after recording demographic details. Direct microscopy using 10%KOH was performed for the presence of branched hyaline hyphae and the samples were cultured on Sabourauds dextrose agar for species identification. Results: Among the various clinical types, Onychomycosis was the common clinical type (41.1%) in age group of 20-40years and it was seen predominantly in men. Out of total 112 samples, about 38 subjects were culture positive with dermatophytes strains. Among the isolates, Trichophytonmentagrophyte was the mostcommon (16.96%), followed by T.rubrum (8.03%). Superficial mycotic infection and dermatophyte infection was seen to be more for males as compared to females (P=0.00049). Conclusion: Onychomycosis was the common clinical type. By comparing the strains of the clinical types we can classify the disease according to its severity and occurrence, which will further help in designing effective treatment strategies. Since fungal culture takes time, direct microscopy using KOH for fungal elements helps in starting empirical treatment. Appropriate management for fungal infection should be done by adapting healthy habits like not sharing the daily utilities and cleaning body on regular basis.